2007
DOI: 10.1002/app.25839
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing composite of multiwalled carbon nanotubes and POE‐g‐AA prepared via melting method

Abstract: Multiwalled carbon nanotubes (MWNTs) with acyl chloride functional groups and a metallocene polyethylene-octene elastomer (POE) or an acrylic acid-grafted metallocene polyethylene-octene elastomer (POE-g-AA) were used to prepare hybrids (POE/MWNTs or POE-g-AA/MWNTs) using a melting method, with a view to identify a hybrid with improved thermal properties. Hybrids were characterized using Fourier transform infrared spectroscopy, 13 C solid-state nuclear magnetic resonance, X-ray diffraction, thermogravimetry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…For the analysis of the absorption features, we recorded IR spectra of both CNT-COOH and pyrrole functionalized CNT. The spectra for CNT-COOH show the characteristic CNT absorption peaks similarly to other reports [16,17] at 1505-1560 cm −1 (aromatic ring), 1308 cm −1 (-C-O), and 1640 cm −1 (-C=C-). Moreover, the stretching vibration of the C=O group is identified at 1116 and 1690 cm −1 together with a hydroxyl-stretching weak band at 3300-3500 cm −1 [16].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…For the analysis of the absorption features, we recorded IR spectra of both CNT-COOH and pyrrole functionalized CNT. The spectra for CNT-COOH show the characteristic CNT absorption peaks similarly to other reports [16,17] at 1505-1560 cm −1 (aromatic ring), 1308 cm −1 (-C-O), and 1640 cm −1 (-C=C-). Moreover, the stretching vibration of the C=O group is identified at 1116 and 1690 cm −1 together with a hydroxyl-stretching weak band at 3300-3500 cm −1 [16].…”
Section: Resultssupporting
confidence: 84%
“…The spectra for CNT-COOH show the characteristic CNT absorption peaks similarly to other reports [16,17] at 1505-1560 cm −1 (aromatic ring), 1308 cm −1 (-C-O), and 1640 cm −1 (-C=C-). Moreover, the stretching vibration of the C=O group is identified at 1116 and 1690 cm −1 together with a hydroxyl-stretching weak band at 3300-3500 cm −1 [16]. The band at 1690 cm −1 disappears and strong absorption peaks appear at 1714, 1614, and 1598 cm −1 (pyrrole ring-stretching mode) as a result of the esterification of CNT-COCl with N-(6-hydroxyhexyl)pyrrole.…”
Section: Resultssupporting
confidence: 84%
“…It was reported in various studies that introducing nanotubes in a polymer matrix increased glass transition, melting and thermal decomposition temperatures due to hindered chain and segmental mobility of polymers. [110][111][112][113][114][115] It was observed that the glass transition temperature (T g ) of PU/amide-functionalized MWCNT elastomer composite had increased by 10 C and thermal stability was also improved relative to the unfilled PU properties. 81 In a study, DSC curves of the thermoplastic PU/MWCNT nanocomposites with different mass ratios were recorded.…”
Section: Mechanical Properties Of Pu/cnt Compositesmentioning
confidence: 99%
“…The oxidation favors the formation of phenol groups in MWCNTs from both suppliers; ester groups seem more favorable in case of the MWCNT FC 99 , whereas in the case of the MWCNT BMS 95 the presence of ketones and carboxylic acid groups is predominant. The formation of carbonyl and hydroxyl groups at MWCNTs after the reaction with HNO 3 (and other carbonaceous fibers)50 has been widely described by other groups using different characterization techniques,48, 51–55 where a qualitative increase in FTIR signal intensity in the region of the carbonyl or hydroxyl groups is associated to a discrete increase on the concentration of oxygen atoms at the surface of the carbon nanotubes. This increment has proven to be satisfactory for further reactions of the carbon nanotubes with small molecules51 or with polymer chains 52, 56…”
Section: Resultsmentioning
confidence: 99%